Quality of minimally processed ‘Monalisa’ apples with antioxidants and edible toppings - Oliveira, Álvaro Batista de; Mello-Farias, Paulo; Cantillano, Rufino Fernando Flores; Kirinus, Marines Batalha Moreno; Herter, Flávio Gilberto; Pasa, Mateus da Silveira (Comunicata Scientiae, 2024)
Minimally processed fruits are an alternative to add value to products that are difficult to sell, in addition to facilitateconsumer consumption. The objective is to research pulp browning inhibition in a simulated commercialization of minimally processed ‘Monalisa’ apples, stored in a refrigerated environment. After being sanitized with sodium hypochlorite, the apples were cut and immersed in the following treatments: the control being sodium erythorbate (ES) + A (distilled water); ES + FM (cassava starch 3%); ES + AS (3% sodium alginate); ES + AM (6% waxy maize starch) and ES + AP (3% pine nut starch), all together with 1% calcium chloride. Afterwards, 10 slices were placed in a polyethylene tray, wrapped in stretchable PVC film and stored in a refrigerated chamber at 4 ºC ± 1 ºC and relative humidity of 90 - 95%. Phytochemical evaluations were performed at 0, 3, 6 and 9 days of storage. The applied treatments maintained fruit quality. The treatment with cassava starch and pine nut starch were efficient in preserving the darkening of the fruit pulp on day 9. As for the waxy corn starch treatment, the enzyme activity was lower in the period of 0 and 6 days, maintaining quality and delaying darkening. The control sample (ES + A + CC) stood out during the 9-day period, as there was a decrease in the activity of polyphenoloxidase and peroxidase enzymes.